ANALISIS PROFITABILITAS, UKURAN PERUSAHAAN, PERPUTARAN PIUTANG, RASIO HUTANG DAN OPERATING CYCLE TERHADAP LIKUIDITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2014-2017 - karnadi karnadi (Jurnal Ilmu Akuntansi, 2020)
This study aims to determine the effect of profitability, company size, accounts receivable turnover, debt ratio and operating cycle on liquidity with the analysis method using, Multiple Linear Regression, Multiple Correlation, Determination, t test and F test. From the results of the t test, profitability has an effect on liquidity. Company size affects liquidity. Accounts Receivable Turnover has no effect on liquidity. Debt ratio has no effect on liquidity. Operating Cycle affects liquidity. From the overall test there is an effect of profitability, company size, accounts receivable turnover, debt ratio, operating cycle simultaneously to liquidity.